Synthesis, Characterization and Antibacterial Studies of New Metal Complexes of α-Aminonitriles Derived from P- Chlorobenzaldehyde with 2-Aminopyrimidine - Mohammed H. A. Al-Amery (Journal of Global Pharma Technology, 2018)
New metal ion complexes of some transition metal ions [Mn(II), Ni(II), Cu(II), Zn(II), Cd(II) and Hg(II)] of previously prepared ligand 2-(4-Chlorophenyl)-2-(Pyrimidin-2-Ylamino)Acetonitrile was synthesized. The ligand was prepared by Strecker's procedure which included the reaction of P-Chlorobenzaldehyde with 2-Aminopyrimidine and the structures of the new metal ion complexes were characterized by Elemental Micro Analysis (C.H.N), Chloride Content, FT-IR, UV-Vis spectra, Thermal Gravimetric Analysis (TGA-DTG), flame atomic absorption, molar conductivity as well as magnetic susceptibility measurement. According to the obtained data the probable coordination geometries of these complexes were suggested as octahedral. All complexes were found to be non-electrolyte. The antibacterial activity of the ligands and their metal ion complexes have been studied by screening against various microorganisms, Staphylococcus aureus, Bacillus subtilis (Gram-positive), Escherichia and Pseudomonas aeruginosa (Gram-negativre). Agar (well-diffusion method) was used to determine the activity. The metal ion complexes gave the formulae: [ML2Cl2].nH2O.Keywords: 2-(4-Chlorophenyl)-2-(Pyrimidin-2-Ylamino)Acetonitrile, Transition metal ions.